2023
DOI: 10.15252/embj.2023114587
|View full text |Cite
|
Sign up to set email alerts
|

Diversity matters — extending sound intensity coding by inner hair cells via heterogeneous synapses

Tobias Moser,
Nare Karagulyan,
Jakob Neef
et al.

Abstract: Our sense of hearing enables the processing of stimuli that differ in sound pressure by more than six orders of magnitude. How to process a wide range of stimulus intensities with temporal precision is an enigmatic phenomenon of the auditory system. Downstream of dynamic range compression by active cochlear micromechanics, the inner hair cells (IHCs) cover the full intensity range of sound input. Yet, the firing rate in each of their postsynaptic spiral ganglion neurons (SGNs) encodes only a fraction of it. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…Intensity information is encoded by the number and types of SGNs that are activated in the cochlea. The Ia, Ib, and Ic molecular subtypes defined in mouse 39,40,42 broadly correspond to the anatomically and physiologically defined subtypes described across species 41,94 . We find that the majority of inputs onto octopus cells come from Ia ANFs, which most closely correspond to the low-threshold, high-spontaneous rate population.…”
Section: Discussionmentioning
confidence: 60%
“…Intensity information is encoded by the number and types of SGNs that are activated in the cochlea. The Ia, Ib, and Ic molecular subtypes defined in mouse 39,40,42 broadly correspond to the anatomically and physiologically defined subtypes described across species 41,94 . We find that the majority of inputs onto octopus cells come from Ia ANFs, which most closely correspond to the low-threshold, high-spontaneous rate population.…”
Section: Discussionmentioning
confidence: 60%
“…Further analysis demonstrated that c-Maf and Mafb are also expressed differentially across SGN subtypes during synaptogenesis, which occurs during the first two postnatal weeks of life in mice (Coate et al, 2019; Moser et al, 2023). To mark developing SGN subtypes definitively, we used NetrinG1 Cre/+ , which selectively marks adult Ib and Ic subtypes when combined with the Ai14 Cre-dependent tdTomato reporter (RCL-tdT), consistent with its scRNA-seq expression profile ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, genetically labeled Ia/Ib SGNs show extensive variability in their firing rates (Siebald et al, 2023), possibly due to differences in their local connectivity. Indeed, individual IHC-SGN synaptic structures show extensive heterogeneity in composition, size, and morphology, and in presynaptic calcium channel density (Hu et al, 2020; Liberman et al, 2011; Liberman and Liberman, 2016; Michanski et al, 2019; Moser et al, 2023; Payne et al, 2021). Some of these differences are linked to subtype identity.…”
Section: Introductionmentioning
confidence: 99%
“…This applied to the synthetic ribbons as well as to the AZ-like clusters of Bassoon, RBP2 and Ca V 1.3 Ca 2+ channels. However, all three components exhibited variability beyond the substantial natural heterogeneity found among the IHC AZs (Moser et al , 2023). Functionally, Bassoon and RBP2 co-expression resulted in larger whole-cell Ca V 1.3 currents.…”
Section: Discussionmentioning
confidence: 99%